2020
DOI: 10.1108/ijesm-08-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing enablers and barriers to successfully project control system implementation in petroleum and chemical projects

Abstract: Purpose The purpose of this study is to analyze the interaction between the enablers and barriers to successful project control system (PCS) implementation in petroleum and chemical projects and to provide a knowledge-based foundation for the evaluation of the dominant factors of PCS success. Design/methodology/approach An integrated approach of interpretive structural modeling (ISM) and cross-impact matrix multiplication applied to classification (Matrice d’Impacts Croisés Multiplication Appliquée à un Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Therefore, the main objectives of this study were: (1) to investigate the PCS elements that are critical to achieve project success; and (2) to identify the significant enablers and barriers of PCS success by examining the impact of these enablers and barriers on each elements of PCS. Based on the results of a previous studies (Jawad and Ledwith, 2020, 2021), three enablers, six barriers and six elements of PCS success were selected to further study in this research.…”
Section: Discussion and Final Research Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the main objectives of this study were: (1) to investigate the PCS elements that are critical to achieve project success; and (2) to identify the significant enablers and barriers of PCS success by examining the impact of these enablers and barriers on each elements of PCS. Based on the results of a previous studies (Jawad and Ledwith, 2020, 2021), three enablers, six barriers and six elements of PCS success were selected to further study in this research.…”
Section: Discussion and Final Research Modelmentioning
confidence: 99%
“…Their study identified a total of nine enablers and 15 barriers that related to PCS success (Jawad et al, 2018). A follow-on study was then conducted using interpretive structural modeling (ISM) to examine the relationship between these enablers and barriers and to identify the most dominant ones (Jawad and Ledwith, 2020). This study identified (3) dominant enablers that drive successful PCS: 1) "Skilled and experienced project team members", 2) "Explicitly defined roles of project team members" and 3) "An accurate Work Breakdown Structure (WBS)".…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies address the significance of project control in achieving project objectives. These studies have demonstrated that project performance can be enhanced if devoted PCS is set up and successfully implemented (Jawad et al , 2018; Jawad and Ledwith, 2020; Ling and Ang, 2013). An effective PCS can decrease project schedule slippage by 15% and improve project cost by 10% (Ekambaram, 2006; Ford et al , 2007).…”
Section: Introductionmentioning
confidence: 99%